Hellen Papanicolas, 2002, An amulet of Greek earth: Generations of immigrant folk culture, Swallow Press, Ohio University Press, xiii+316pp, notes, selected glossary of Greek words, index - Milios, Evangelos (The Greek Review of Social Research, 2003)
Δε διατίθεται περίληψη / no abstract available